Determinant Factor Managerial Effectiveness: A Systematic Literature Review - Sutarto, Bambang; Rizqahu, Argosawwa (The Eastasouth Management and Business, 2025)
The purpose of this article is to analyze through a systematic literature review of 5 reputable international journal papers related to determinants of managerial effectiveness factors, which aim to describe and identify important factors in achieving managerial effectiveness. The method used is a systematic literature review of 5 scientific articles published in international journals with the stages of searching for journals in databest connected papers online, then selecting and categorizing themes, comparing, synthesizing theories and drawing conclusions. The results of the systematic analysis of the literature review show that the interaction between personality, experience, and managerial ability is crucial in shaping managerial effectiveness. Personality traits form the basic framework, while experience refines practical application and managerial ability drives performance adaptation.